Parenting Style to Reduce Academic Stress in Early Childhood during The New Normal - Sari, Uni Kartika; Sulistiyaningsih, Retno (Universitas Muhammadiyah Surakarta, 2023)
Abstract. At home, the role of parents is not only as a facilitator but also as a coach and companions in children's activities during the new normal era, especially in learning activities. The purpose of this study is to analyse parenting style to reduce academic stress in early childhood age 3 to 6 years during new normal era. This study uses a method derived from the literature review (SLR), the systematic mappingstudy (SMS). A systematic mapping study is a systematic literature review that using predetermined protocols and filters. The research conducted an online search on the indexed electronic database of Google Scholar. The Researcher used 14 main articles according to the research topic and matched the keywords. However, other sources that support the theory of child development and parenting style are still needed. The results showed that good parenting through active involvement, responsiveness, caring, sensitivity to children's emotions, communication, and empowerment would ensure positive developmental outcomes during the new normal era. The parenting style to reduce the level of academic stress in early childhood during the new normal by maintaining positive relationships and interactions, facilitating children's needs for remote learning, providing learning assistance, encouraging children to express emotions, creating constructive family rules, showing appreciation to children and parents actively participating in seminars and training on positive parenting. Findings have implications for parents whose children are actively learning and try to use positive parenting style to reduce academic stress during the new normal.Keywords: Parenting style; academic stress; early childhood; new normal; covid-19.